Las Fábulas de Manuel Zapata Olivella: Estrategia didáctica para la sana convivencia. (2023)
This work is based on voluntary pedagogical practices with the children's group of the Artistic and Cultural Foundation Son de mi Tierra, located in the city of Bogota, in the district of Ciudad Bolivar. Where through theatrical games, understanding and reading of the Fables of Tamalameque by Manuel Zapata Olivella, contributes to conflict resolution, for a healthy coexistence in that organization. In this systematization, the phases for the development of a significant experience of Oscar Jara are taken, starting from the starting point where the children actively participate in the experience and concludes by showing how the games and the fables contributed in a significant way to the coexistence of the children of the aforementioned foundation